2004
DOI: 10.1108/01425450410544515
|View full text |Cite
|
Sign up to set email alerts
|

Bounded choices in work and retirement in Australia

Abstract: Australia, together with most other developed and developing countries, faces a difficult demographic pattern in the first half of the twenty‐first century, due to a low and declining birth rate and an ageing population. This has led to an ageing workforce, with a relative shortage of younger entrants. One issue for government is what further steps they could initiate to persuade more people to remain in the labour force beyond the currently median retiring age of around 55 years. Employers will need to consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 12 publications
0
46
0
Order By: Relevance
“…Therefore, writers such as Price (2000) argue that rather than viewing retirement as a unitary event, it could be seen as one of the many discontinuities women face in their lives and that it should therefore be regarded as a transition that takes place 'in the context of multiple family responsibilities and past professional changes' (Price, 2000, p. 96). These factors include: personal health (Arber, 2004;Arber and Cooper, 1999), family and caring responsibilities (Price, 2003;Wong and Hardy, 2009;Loretto and Vickerstaff, 2011), financial issues (Kim and Moen, 2002;O'Rand, 1996;Patrickson and Ranzijn, 2004;Perkins, 2003;Price, 2000;Smeaton and McKay, 2003), employment policies and discrimination (Armstrong-Stassen, 2008;Patrickson and Hartmann, 1996;Patrickson and Ranzijn, 2004;Soidre, 2005) and institutional factors (Loretto and White, 2006;McNair, 2006) that inhibit or enable choice with regard to work and retirement activity. These factors include: personal health (Arber, 2004;Arber and Cooper, 1999), family and caring responsibilities (Price, 2003;Wong and Hardy, 2009;Loretto and Vickerstaff, 2011), financial issues (Kim and Moen, 2002;O'Rand, 1996;Patrickson and Ranzijn, 2004;Perkins, 2003;Price, 2000;Smeaton and McKay, 2003), employment policies and discrimination (Armstrong-Stassen, 2008;Patrickson and Hartmann, 1996;Patrickson and Ranzijn, 2004;Soidre, 2005) and institutional factors (Loretto and White, 2006;…”
Section: Understanding Women's Careers and Retirementmentioning
confidence: 99%
“…Therefore, writers such as Price (2000) argue that rather than viewing retirement as a unitary event, it could be seen as one of the many discontinuities women face in their lives and that it should therefore be regarded as a transition that takes place 'in the context of multiple family responsibilities and past professional changes' (Price, 2000, p. 96). These factors include: personal health (Arber, 2004;Arber and Cooper, 1999), family and caring responsibilities (Price, 2003;Wong and Hardy, 2009;Loretto and Vickerstaff, 2011), financial issues (Kim and Moen, 2002;O'Rand, 1996;Patrickson and Ranzijn, 2004;Perkins, 2003;Price, 2000;Smeaton and McKay, 2003), employment policies and discrimination (Armstrong-Stassen, 2008;Patrickson and Hartmann, 1996;Patrickson and Ranzijn, 2004;Soidre, 2005) and institutional factors (Loretto and White, 2006;McNair, 2006) that inhibit or enable choice with regard to work and retirement activity. These factors include: personal health (Arber, 2004;Arber and Cooper, 1999), family and caring responsibilities (Price, 2003;Wong and Hardy, 2009;Loretto and Vickerstaff, 2011), financial issues (Kim and Moen, 2002;O'Rand, 1996;Patrickson and Ranzijn, 2004;Perkins, 2003;Price, 2000;Smeaton and McKay, 2003), employment policies and discrimination (Armstrong-Stassen, 2008;Patrickson and Hartmann, 1996;Patrickson and Ranzijn, 2004;Soidre, 2005) and institutional factors (Loretto and White, 2006;…”
Section: Understanding Women's Careers and Retirementmentioning
confidence: 99%
“…Yet, less than ten percent of employers reported introducing any flexible working arrangements such as part-time or casual work, or phased retirement programs (Parsons and Mayne 2001). Patrickson and Ranzijn (2004) argued that offering flexible work to older workers close to their retirement decision was viewed by them as an attractive option. In overseas research, older UK professionals found different forms of working (especially freelancing, consulting and self-employment) to be attractive employment options (Platman 2004), and may influence their intention to continue working longer.…”
Section: (D) Flexible Work Arrangementsmentioning
confidence: 99%
“…Such studies may be able to identify a profile of individuals who are attracted by certain benefits and thus guide organizations in how to tailor the compensation package strategically to attract specific types of individuals. Many countries across the globe will be faced with labor shortages and an aging workforce (Osman-Gani and Chan 2009; Patrickson and Ranzijn 2004). Due to these challenges, employers may need to consider persuading and attracting older employees to remain in the labor force beyond the current retirement age.…”
Section: Practical Implication and Directions For Future Researchmentioning
confidence: 99%